HUBUNGAN KADAR HEMOGLOBIN IBU HAMIL TERHADAP BERAT BADAN BAYI BARU LAHIR - Nurana, Sitti; Husnah, Nurul; Hamang, Sitti Hadriyati; Akbar, Nurlina (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2025)
The Ministry of the Republic of Indonesia (Kemenkes) reported that the Maternal Mortality Rate (MMR) in 2022 was around 183/100,000 live deaths. The high MMR and Infant Mortality Rate (IMR) are generally influenced by the high number of mothers who have high risk and poor obstetric history in pregnancy and lack of early detection in pregnancy. The impact on babies can include obstacles to fetal growth and development in the womb, abortion, premature birth, LBW, infection in newborns and growth after birth experiencing difficulties and infant death. This study aims to determine how hemoglobin (Hb) levels in pregnant women are related to newborn weight (LBW), bleeding during childbirth, low birth weight (LBW), non-ideal IQ, babies who are susceptible to infection, and malnutrition. During pregnancy Plasma increases quite significantly then the concentration of hemoglobin and hematocrit decreases somewhat, during pregnancy as a result the overall blood viscosity will decrease, the average hemoglobin concentration at term is 12.5 g / dl and in about 5% of women the concentration is less than 11.0 g / dl, therefore the hemoglobin concentration below 11 g / dl, especially at the end of pregnancy should be considered abnormal and is usually caused by iron deficiency and not due to hypervolemia of pregnancy According to the Ministry of Health (2005), several factors that cause anemia in pregnant women include bleeding during childbirth, low birth weight (LBW), poor IQ, the tendency of babies to be infected, and malnutrition. Hemoglobin and hematocrit concentration during pregnancy this study aims to determine the relationship between hemoglobin (Hb) levels of pregnant women and newborn weight, the variables to be studied are Hb levels and newborn weight. During pregnancy, plasma increases significantly, so the concentration of hemoglobin and hematocrit decreases slightly. During pregnancy, the overall blood viscosity decreases. The average hemoglobin concentration at term is 12.5 g/dl and in about 5% of women the concentration is less than 11.0 g/dl. Therefore, hemoglobin concentrations below 11 g/dl, especially at the end of pregnancy, should be considered abnormal and are usually caused by iron deficiency and not due to pregnancy hypervolemia. This study will be conducted at the Rappokalling Health Center, Makassar. The type of research used is an analytical survey with a cross-sectional study approach. Sampling is non-probability sampling. The results of statistical tests with chy square show a significant relationship between hemoglobin levels in pregnant women and newborn weight with a P-value of 0.001